EFFECT OF CORPORATE GOVERNANCE ON FINANCIAL INFORMATION OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - MAINOMA, MOHAMMED AKARO; AZA, SOLOMON M.; AME, JACOB.O.; AZABWONUWO, AZAKI JOB (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study investigates the effect of corporate governance attributes on financial information disclosure among listed Deposit Money Banks (DMBs) in Nigeria over a ten-year period (2014–2023). Adopting an ex post facto research design and utilizing secondary data from audited annual reports, the study employs a fixed effects panel regression model with robust standard errors to account for firm-level heterogeneity and endogeneity. Key governance variables examined include board financial expertise, board independence, board gender diversity, audit committee meetings, and managerial ownership, with firm size and profitability included as control variables. The findings reveal that board financial expertise, board independence, and audit committee meetings have significant positive effects on financial disclosure, while managerial ownership exerts a significant negative influence. Board gender diversity, although positively related to disclosure, was not statistically significant. The results underscore the importance of effective internal governance mechanisms in promoting transparency and accountability in the Nigerian banking sector. The study recommends strengthening board independence and financial expertise, enhancing audit committee functionality, and improving regulatory oversight on ownership structures to foster robust disclosure practices.